Revealing the rural multifunctionality declining and its causes in depopulated regions of Northeast China: a case study of Heilongjiang Province - Dongmei Li; Qing Wen; Yue Qi; Guoming Du (Humanities & Social Sciences Communications)
Abstract As the main form of global rural decline, the impact of rural population loss on the overall level and trend of rural multifunction is still unclear. Thus, it is crucial to reveal the characteristics and influencing factors of rural multifunction changes in depopulation areas which is important to actively deal with depopulation and promote sustainable development in rural areas. Based on an evaluation of rural multifunctionality from 2000 to 2020, the spatial statistical analysis method and a geographical model were used to reveal the declining characteristics of rural multifunction in the depopulation area, as well as the effects of the influencing factors in the whole region and under various population size areas. The results show that demographic changes had a significant impact on rural multifunction development. Compared to areas with population growth, the weakening of rural multifunctionality was more likely to occur in counties with depopulation. The negative impact of population shrinkage on rural multifunction development was shown in our results as an inverted “U” shape. In the process of demographic shrinkage, the dominant factors affecting rural multifunctionality in the whole region tended to be diversified, but the population urbanization rate was always the main factor. Among regions with different population sizes, natural factors played important roles in the development of rural multifunction, and depopulation enhanced the impact of economic factors. The interaction effect of natural, social, and economic factors was stronger than that of a single factor in rural multifunction. In the process of depopulation, the interaction effect was more and more polarized. The interaction effect of economic and natural factors enhanced, but which was the most stable in mid-population-size areas. Thus, to alleviate rural decline and realize rural revitalization, the trend of demographic change should be given attention to keep a moderate population size, as well as we should actively deal with the impact of population shrinkage on rural multifunction according to different stages of population shrinkage.